National power and the structure of foreign trade - Hirschman, Albert O. (Berkeley ; Los Angeles : University of California Press, 1969)
This essay was written in 1942 at the University of California, Berkeley, under a fellowship granted by the Rockefeller Foundation. It is an outgrowth of the authors collaboration with the trade Regulation Project.
Includes bibliographical footnotes and index.
rpm 23/01/2018
Loans
Keywords: Foreign trade